The simultaneous effect of firm capabilities and competitive strategies on export performance: the role of competitive advantages and competitive intensity - Keskin, Halit; Ayar Senturk, Hayat; Tatoglu, Ekrem; Golgeci, Ismail; Kalaycioglu, Ozan; Etlioglu, Hatice Tuba (EMERALD GROUP PUBLISHING LTD, 2021)
Purpose This study aims to determine the simultaneous effect of exporting firms' competitive strategies and capabilities on the achievement of competitive advantages and export performance under the boundary conditions of competitive intensity. In so doing, the study combines the alternative theoretical lenses of the resource-based view (RBV) and the structure-conduct-performance (SCP) paradigm. Design/methodology/approach Primary data were obtained from 281 Turkish manufacturer-exporter firms operating in different sectors and located in several regions of the country. Structural equation modeling was utilized to test our conceptual framework, which combined the effects of RBV-based and SCP-based factors on competitive advantages and export performance under the moderating influence of competitive intensity. Findings This study reveals that unique firm capabilities, specifically informational, relational, and marketing capabilities, and competitive strategies, including differentiation and cost leadership, provide export firms with a competitive advantage and improve their export performance in foreign markets. Furthermore, competitive advantages partially mediate the effects of competitive strategies and unique firm capabilities on export performance. Finally, unexpectedly, and contrary to most of the existing literature, we find that competitive intensity negatively moderates the link between service advantages and export performance. Originality/value This research offers a comprehensive view of manufacturer-exporter firms' export performance by accounting for the overlooked simultaneous effect of firm capabilities and competitive strategies through the mediation of competitive advantages and under the boundary conditions of competitive intensity.
Keywords: Export marketing; International marketing; Resource-based view; Competitive strategy; Competitive advantage; MARKETING CAPABILITIES; RESOURCES; DETERMINANTS; LEVEL; MODEL; INNOVATION; FRAMEWORK; QUALITY; VIEW; Business & Economics